2023
DOI: 10.1200/op.22.00355
|View full text |Cite
|
Sign up to set email alerts
|

Team Science Principles Enhance Cancer Care Delivery Quality Improvement: Interdisciplinary Implementation of Breast Cancer Screening Shared Decision Making

Abstract: PURPOSE: Implementing shared decision making (SDM), recommended in screening mammography by national guidelines for women age 40-49 years, faces challenges that innovations in quality improvement and team science (TS) are poised to address. We aimed to improve the effectiveness, patient-centeredness, and efficiency of SDM in primary care for breast cancer screening. METHODS: Our interdisciplinary team included primary and specialty care, psychology, epidemiology, communication science, engineering, and stakeho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…This requires mechanisms to both incorporate different perspectives and integrate their implications. Such mechanisms include prebriefs and cross-checking in direct patient care, 16 decision support systems for diagnoses (Burnside), 17 the creation of pediatric-onco dental teams to address oral infection (Bledsaw), 18 and collaborative multidisciplinary smoking cessation treatment programs (Cooper). 19 Are Various Roles and Responsibilities Clear?…”
Section: What Competencies Are Required?mentioning
confidence: 99%
“…This requires mechanisms to both incorporate different perspectives and integrate their implications. Such mechanisms include prebriefs and cross-checking in direct patient care, 16 decision support systems for diagnoses (Burnside), 17 the creation of pediatric-onco dental teams to address oral infection (Bledsaw), 18 and collaborative multidisciplinary smoking cessation treatment programs (Cooper). 19 Are Various Roles and Responsibilities Clear?…”
Section: What Competencies Are Required?mentioning
confidence: 99%
“…In a single-site project using two Plan-Do-Study-Act cycles, women and their primary care physicians reported improved shared decision making after use of the adapted B~Care 2.0, a web-based tool to share key facts about screening mammography and depict personalized risk/benefit assessments. 1 A key strength of the adapted tool was full integration into the health system's electronic health record. Iterative use of Plan-Do-Study-Act cycles resulted in high adoption and end-user satisfaction.…”
mentioning
confidence: 99%